The Utilization of Expired Instant Noodles as A Subtitute for Milled Corn in Concentrate of Weight Gain and Physiological Status of Goat - Wulan, Sri; Nirwana, Nirwana; Zainal, Zainal (FAPETKAN UNTAD, 2021)
This research was conducted in the experimental cage owned by CV. Prima BREED in Tondo Village, Mantikulore Subdistrict, Palu City, Central Sulawesi Province from January 15 to March 15, 2019. This research aims to find out the effect of expired instant noodles as a substitute for milled corn on body weight gain and the physiological status of Kacang goats. The number of livestock used in this research amounted to 15 local female goats aged Â± 10 months with a body weight range between 9.92 to 19.25 kg. The environmental design used in this research was a Randomized Block Design (RBD) consisting of 5 treatments and repeated 3 times as a group. The treatments that were tested were P1 = instant noodles to replace milled corn by 100% in a concentrate arrangement; P2 = Instant noodles replace milled corn by 75% in a concentrate arrangement; P3 = Instant noodles replace milled corn by 50% in a concentrate arrangement; P4 = Instant noodles replace milled corn by 25% in the concentrate arrangement and P5 = Instant noodles replace milled corn by 0% in the concentrate arrangement. The results of the analysis of variance show that replacing milled corn with expired instant noodle waste up to 100% in concentrate does not have a negative effect on body weight gain, dry matter consumption, ration efficiency, body temperature, respiration frequency, and pulses frequency of Kacang goats.